2019
DOI: 10.3390/molecules24071314
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation of Chaenomeles japonica: A Step towards Production of Polyphenol-rich Extracts Showing Antioxidant and Antimicrobial Activities

Abstract: A protocol for C. japonica micropropagation with a confirmation of genome size stability of the in vitro-propagated plantlets was developed. The highest number of shoots multiplied in vitro was obtained on Murashige & Skoog medium (MS) with 1.0 mg L−1 N6-benzyladenine plus 1.0 mg L−1 indole-3-acetic acid. The highest number of roots was observed for the shoots on MS with 15 g L−1 sucrose plus 1.0 mg L−1 indole-3-acetic acid. The acclimatization rate was significantly high. The qualitative HPLC analyses con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…Similar amounts (from 42.90% to 50.90%) of hydroxycinnamic acids in quince leaves were found in a recent study of Chojnacka and co-authors [ 13 ]. The predominant compound of this group in all cultivars was chlorogenic acid, and this is in agreement with other studies [ 13 , 19 ]. The amount of flavonols in all cultivars was around 30% of total phenols.…”
Section: Discussionsupporting
confidence: 93%
“…Similar amounts (from 42.90% to 50.90%) of hydroxycinnamic acids in quince leaves were found in a recent study of Chojnacka and co-authors [ 13 ]. The predominant compound of this group in all cultivars was chlorogenic acid, and this is in agreement with other studies [ 13 , 19 ]. The amount of flavonols in all cultivars was around 30% of total phenols.…”
Section: Discussionsupporting
confidence: 93%
“…This confirmed the genome size stability of micropropagated material, which is in agreement with the results obtained by ISSR, revealing no somaclonal variation in plantlets. Similar stability has been found for numerous species produced in vitro, including trees and shrubs, e.g., oak, eucalyptus, banana, olive, and Japanese quince [54][55][56][57][58].…”
Section: Flow Cytometrysupporting
confidence: 75%
“…In addition, rutin showed the ability to enhance the antibacterial activity of other phenols and antibiotics [51,52]. JQ fruit extracts had a stronger inhibitory effect against E. coli ATCC 25922 and P. aeruginosa ATCC 27853 than S. aureus ATCC 25923 [20]. The results of our study showed that only 'Rasa' extracts have similar activity, but 'Darius' and 'Rondo' extracts had the opposite effect, stronger inhibits S. aureus (ATCC 25923).…”
Section: Propertiesmentioning
confidence: 60%
“…Numerous studies have shown that the phenolic compounds are promising biologically active compounds that may act as a new type of antimicrobial agent [17][18][19]. Kikowska and co-authors demonstrated the antibacterial activity of JQ leaf and fruit extracts against four bacteria strains Staphylococcus aureus (ATCC 25923), Escherichia coli (ATCC 25922), Pseudomonas aeruginosa (ATCC 27853), and one yeast strain Candida albicans (ATCC 10231) [20]. The antibacterial activity of other species such as Chaenomeles speciosa essential oil against 10 microorganisms has been studied [21].…”
Section: Introductionmentioning
confidence: 99%